2010
DOI: 10.1007/s11746-010-1612-z
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Screening of Intact Castor Seeds by Viscosity Using Time‐Domain NMR and Chemometrics

Abstract: Castor is one of the most promising non-edible oil crops, due to its high oil content and since it can be grown on marginal lands and in a semi-arid climate. However, the high content of ricinoleic acid results in an extremely high viscosity of castor-based biodiesel. In this study, we report on the development of a rapid and non-destructive method for large-scale screening of intact castor seeds according to their viscosity by time domain NMR and chemometrics. A qualitative principal component analysis model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Since all the samples per type of oil were very closely clustered, the name of only one of the oil samples for each of the oils is shown on the plot, to facilitate its interpretation. Still, PC 2 revealed qualitative information, meaning high or low values of PC 2 correlated to high or low viscosities, as shown in a previous study [59]. In that study, a PCA model was suggested for rapid large-scale screening of castor seeds according to viscosity.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Since all the samples per type of oil were very closely clustered, the name of only one of the oil samples for each of the oils is shown on the plot, to facilitate its interpretation. Still, PC 2 revealed qualitative information, meaning high or low values of PC 2 correlated to high or low viscosities, as shown in a previous study [59]. In that study, a PCA model was suggested for rapid large-scale screening of castor seeds according to viscosity.…”
Section: Resultsmentioning
confidence: 70%
“…The PC 2 scale of the plot was enlarged, in order to focus on the area of interest, therefore the castor biodiesel sample is not shown. Following the established correlation of PC 2 and viscosity [59], it is clearly demonstrated, that residues of water and/or methanol lead to lower than expected biodiesel viscosities, whereas high acylglycerol content lead to the opposite effect.…”
Section: Resultsmentioning
confidence: 87%
“…It was established in the past that mono-exponential T 2 values of FAMEs correlate with their viscosity for the same temperature [ 30 , 31 ]. Table 4 presents the mono-exponential T 2 s for the saturated FAMEs and dynamic viscosities, η , according to [ 20 ], at T m + 5 K and at 313 K for reference.…”
Section: Resultsmentioning
confidence: 99%
“…Germplasm characterization would also be easier if fast, nondestructible, and reliable screening methods were developed. An example is the quick and nondestructive method for estimating ricinoleic fatty acid content by nuclear magnetic resonance in seeds (Berman et al, 2010).…”
Section: Geneticsmentioning
confidence: 99%